(untitled) (Journal of Hama University, 2026)
Abomasum Diseases have an important economic role especially Right Abomasal Volvulus because of high costs of treatment and retreat milk production, in addition to treat chronic cases for the animal. Generally Right Abomasal Volvulus (RAV) in diary cows accures as a result of distubance in the movement and empting, and to estimate that movement,I had been done absorbation test using a substance that is not affected via stomach , but is almost completely absorbed in the small intestine without metabolism, where detected in blood. The substance is (D-xylose), consider as indicator of effect of Flunixin Meglumine on abomasal empting rate of RAV post surgical operation. The study inudued 16 Right Abomasal Volvulus infected cows had been tested, divided into tow groups, second Group had been given Flunixin Meglumine with a dose 2.2 mg/kg of body weight by injection in muscle, the First group was not given any medication(G1 control). During surgical,D-xylose had been injected directly in abumasum with a dose 1ML/kg of body weight at G1and G2, samples of blood were taken before an hour of surgical and every 60 minutes over 10 hours post surgical operation. samples were examined using spectrophotometre technique, it was reported an increase in the concentration of anzymes Ck-Ast at tow groups. Clinical examination of groups post surgical observed in group (2) an increase in the movement of rumin in a shorter time compare with group (1).